2014
DOI: 10.1371/journal.pone.0095237
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Hippocampus in Novel Rat Model of Febrile Seizures

Abstract: Febrile seizures (FS) are the most common type of convulsive events in infants and young children, but the precise underlying genetic mechanism remains to be explored. To investigate the underlying pathogenic factors in FS and subsequent epilepsy, alterations in gene expression between the two new strains of rats (hyperthermia-prone [HP] vs hyperthermia-resistant [HR]), were investigated by using the Whole Rat Genome Oligo Microarray. This process identified 1,140 differentially expressed genes (DEGs; 602 upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The high demand for low-cost sequencing has led to the development of high-throughput technologies such as next-generation sequencing [ 50 ]. Transcriptome sequencing is one such powerful and cost-effective tool in generating large-scale transcriptome data that may be used in developing molecular markers and in identifying novel genes in model [ 35 , 51 ] and non-model [ 52 , 53 ] organisms. To our knowledge, the present study is the first attempt to perform de novo assembly and to conduct a comprehensive characterization of the comprehensive transcripts of swamp buffalo.…”
Section: Discussionmentioning
confidence: 99%
“…The high demand for low-cost sequencing has led to the development of high-throughput technologies such as next-generation sequencing [ 50 ]. Transcriptome sequencing is one such powerful and cost-effective tool in generating large-scale transcriptome data that may be used in developing molecular markers and in identifying novel genes in model [ 35 , 51 ] and non-model [ 52 , 53 ] organisms. To our knowledge, the present study is the first attempt to perform de novo assembly and to conduct a comprehensive characterization of the comprehensive transcripts of swamp buffalo.…”
Section: Discussionmentioning
confidence: 99%
“…Genes important in these processes included, CCL-2 , CCL-3 , ILr10-a /b, C1qa , and Cr1l . Febrile seizures in rats also show a robust immune response directly after exposure to HT [ 49 , 55 ]. Similarly, electrical kindling of the dentate gyrus as a model for TLE, showed overlap in biological processes with our genelists.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that HP rats have a low seizure threshold and experience spontaneous seizures [19]; the low seizure threshold might be associated with the expression levels and patterns of numerous genes, including a group of metabolism-related genes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Using this rat model, we identified numerous FS susceptibility genes related to metabolism [20]. In this study, we measured particular metabolic parameters and the expression of key genes that are related to metabolism in HP and wild-type (WT) rats.…”
Section: Introductionmentioning
confidence: 99%